2022
DOI: 10.1002/cbdv.202100917
|View full text |Cite
|
Sign up to set email alerts
|

Alashanoids O–S, seco‐Humulane and Eremophilane Sesquiterpenoids from Syringa pinnatifolia

Abstract: Five new sesquiterpenoids, alashanoids O–S (1–5), along with three known analogs (6–8) were isolated from the peeled stems of Syringa pinnatifolia. Their structures were elucidated by analysis of extensive spectroscopic data including ESI‐MS, 1D, 2D NMR. The absolute configurations were determined by comparing its experimental and calculated electronic circular dichroism, calculated OR, calculated NMR, and single crystal X‐ray diffraction data analysis. Compounds 1 and 2 belong to the seco‐humulane type and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…There were a few eremophilane dimers reported from several genera such as Ligularia, [18 -20] Incarvillea, [21] and Eremophila, [22] but none has been described in Oleaceae except for syringenes AÀ L from SP. [15] Therefore, compared to humulane such as zerumbone, and alashanoids AÀ S, [9,11,12,14] dimeric eremophilane might serve as a more characteristic chemical marker to distinguish SP from other Syringa species, which provides another chemical evidence to support the classification controversy for previous methods. [23]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were a few eremophilane dimers reported from several genera such as Ligularia, [18 -20] Incarvillea, [21] and Eremophila, [22] but none has been described in Oleaceae except for syringenes AÀ L from SP. [15] Therefore, compared to humulane such as zerumbone, and alashanoids AÀ S, [9,11,12,14] dimeric eremophilane might serve as a more characteristic chemical marker to distinguish SP from other Syringa species, which provides another chemical evidence to support the classification controversy for previous methods. [23]…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed that terpenoids in particular sesquiterpenoids are the most representative constituents of SP, [10–14] and more than 10 types of sesquiterpenoids have been described from SP so far, including humulane, eremophilane, caryophyllane, and pinnatane, which are specific constituents used to distinguish SP from other Syringa species. However, no dimeric sesquiterpenoid was discovered in the genus until our recent report of dimeric eremophilanes syringenes A−L from SP, which focus on the bioactivities and mechanisms of antitumor effect [15] .…”
Section: Introductionmentioning
confidence: 99%
“…The methods of quantum chemical calculation were previously reported . Briefly, the Gaussian 16 software and SYBYL-X 2.0 program were used to perform the theoretical calculations.…”
Section: Methodsmentioning
confidence: 99%
“…The methods of quantum chemical calculation were previously reported. 48 Briefly, the Gaussian 16 software and SYBYL-X 2.0 program were used to perform the theoretical calculations. A random conformational search of compound 1 was carried out using a MMFF94s molecular force field within 6 kcal/mol energy, which afforded 31 and 24 conformers for (4S)-1 and (4R)-1 respectively.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Solvent not shown, CDCl Tada et al 18 Naya et al 19 Bohlmann et al 20 Tada et al 7 and Sato et al 21 Tada et al 7 and Sato et al 21 Tada et al 23 Tada et al 23 Bohlmann et al 20 Bohlmann et al 20 Novotný et al 17 and Samek et al 24 Bohlmann et al 20 Yamakawa and Satoh 6 Zalkow et al 25 Tori 13 and Saito et al 14 Bohlmann and Ziesche 31 Guerriero and Pietra 32 Guerriero and Pietra 32 Guerriero and Pietra 32 Guerriero and Pietra 32 of alashanoid Q (62) was analyzed by x-ray. 46 The ORD spectra of compounds 66 and 67 were measured. 24 The data of four 10αH-6β-acyloxyfuranoeremophilan-9-ones, 68 to 71, are found in Table 17 (Figure 5).…”
Section: Refmentioning
confidence: 99%